István Győrkös, a permanent target of law enforcement surveillance (Academic Journal of Internal Affairs, 2018)
The author provides an overview of how István Győrkös, a recently apprehended militant neo-Nazi and his followers have been inspected by law enforcement agencies for a quarter century.
Keywords: law enforcement; target; neo-Nazi